loco encodes an RGS protein required for Drosophila glial differentiation. - Granderath, S.; Stollewerk, A.; Greig, S.; Goodman, C.S.; O'Kane, C.J.; Klambt, C. (Development, 1999)
In Drosophila, glial cell development depends on the gene glial cells missing (gcm). gcm activates the expression of other transcription factors such as pointed and repo, which control subsequent glial differentiation. In order to better understand glial cell differentiation, we have screened for genes whose expression in glial cells depends on the activity of pointed. Using an enhancer trap approach, we have identified loco as such a gene. loco is expressed in most lateral CNS glial cells throughout development. Embryos lacking loco function have an normal overall morphology, but fail to hatch. Ultrastructural analysis of homozygous mutant loco embryos reveals a severe glial cell differentiation defect. Mutant glial cells fail to properly ensheath longitudinal axon tracts and do not form the normal glial-glial cell contacts, resulting in a disruption of the blood-brain barrier. Hypomorphic loco alleles were isolated following an EMS mutagenesis. Rare escapers eclose which show impaired locomotor capabilities. loco encodes the first two known Drosophila members of the family of Regulators of G-protein signalling (RGS) proteins, known to interact with the alpha subunits of G-proteins. loco specifically interacts with the Drosophila alphai-subunit. Strikingly, the interaction is not confined to the RGS domain. This interaction and the coexpression of LOCO and Galphai suggests a function of G-protein signalling for glial cell development.